2016
DOI: 10.1002/jmri.25423
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of myocardial stiffness in hypertensive porcine hearts using MR elastography

Abstract: Purpose To determine alteration in left ventricular (LV) myocardial stiffness (MS) with hypertension (HTN). Cardiac magnetic resonance elastography (MRE) was used to estimate MS in HTN induced pigs and MRE-derived MS measurements were compared against LV pressure, thickness and circumferential strain. Materials and Methods Renal-wrapping surgery was performed to induce HTN in 8 pigs. LV catheterization (to measure pressure) and cardiac MRI (1.5T; gradient echo-MRE and tagging) was performed pre-surgery at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Isotropic myocardial shear stiffness has successfully been measured from MRE experiments 11,15,16,[66][67][68] and so it is assumed that sufficient wave propagation can be achieved experimentally. However, the loading applied to the LV model in this experiment is idealised and does not necessarily represent the true harmonic motion that would occur in the left ventricle during cardiac MRE.…”
Section: Discussionmentioning
confidence: 99%
“…Isotropic myocardial shear stiffness has successfully been measured from MRE experiments 11,15,16,[66][67][68] and so it is assumed that sufficient wave propagation can be achieved experimentally. However, the loading applied to the LV model in this experiment is idealised and does not necessarily represent the true harmonic motion that would occur in the left ventricle during cardiac MRE.…”
Section: Discussionmentioning
confidence: 99%
“…Renal wrapping surgery was performed in porcine animals to induce hypertension and hypertrophy, which eventually leads to heart failure. Cine MRE data and invasive pressure measurements were obtained at baseline, 1 month and 2 months post‐surgery . This study demonstrated that MRE‐derived stiffness increased linearly with thickness and pressure, and also showed that stiffness during end‐systole and end‐diastole was significantly higher at months 1 and 2 compared with baseline (Figure ) …”
Section: Applications Of Cardiovascular Mrementioning
confidence: 99%
“…The first harmonic displacement field is obtained by performing the Fourier transform along the temporal dimension of the external waves with a temporal frequency equal to the mechanical excitation frequency in the data acquired with multiple phase offsets to obtain the stiffness maps. 7,46,47,57,62,[67][68][69] Before computing the stiffness maps using the aforementioned inversion strategies, several preprocessing methods are typically performed to remove undesired components from the phase data. Shear waves are of primary interest when estimating the shear stiffness, and therefore the longitudinal waves are removed using the curl operator 62 or bandpass filtering.…”
Section: Stiffness Estimation Based On Approximate Solutions To Thementioning
confidence: 99%
“…MR elastography (MRE) is a novel noninvasive technique to measure the spatial stiffness of soft tissues . MRE images are generated through a three‐step process.…”
mentioning
confidence: 99%
“…12 MR elastography (MRE) is a novel noninvasive technique to measure the spatial stiffness of soft tissues. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] MRE images are generated through a three-step process. First, noninvasive vibrations are applied to tissues by a driver that transmits waves.…”
mentioning
confidence: 99%